Learning RSLogix 5000 Programming (2nd Edition) - Build Robust PLC Solutions with ControlLogix, CompactLogix, and Studio 5000/RSLogix 5000 - Scott, Austin (Packt Publishing, 2020)
This second edition of this book guides you through the technicalities and comes packed with the latest features of Studio 5000, industrial networking fundamentals, and industrial cybersecurity best practices. You'll go through the essential hardware and software components of Logix, before learning all about the new L8 processor model and the latest Studio 5000 architecture to build effective integrated solutions. Entirely new for this edition, you'll discover a chapter on cybersecurity concepts with RSLogix 5000. The book even gets you hands-on with building a robot bartender control system from start to finish. By the end of this Logix 5000 book, you'll have a clear understanding of the capabilities of the Logix platform and be able to confidently navigate Rockwell Automation Literature Library resources.